(untitled) (Al-Academy, 2018)
The scientific studies that deal with Herminutia (interpretation) as the art of reading the interpretation practiced by the recipient after his understanding of the literary texts and works of art that he sees or read them so that these readings to make the act of reading and allow him the opportunity to mature and rational reflection of each text or artistic work. Based on this, the researchers considered the establishment of the problem of their research through the search for the problematic overlap of concepts in the interpretive practices of the literary text? The second chapter dealt with the definition of the term interpretation as well as interpretation as a theory and concept, and then the indicators reached by the research, while the chapter The third of the research procedures and identification of the community and the sample, represented by the literary texts of the writer William Shakespeare, and the results and conclusions reached by the researchers were shown with the list of sources and literature.